Have public policy and family farming been an unhappy marriage for the past 20 years? - Santiago Andrés Roa-Ortiz; Cesar Augusto Forero Camacho; Roger Alonso Bautista Cubillos; Andrés Felipe Zabala Perilla (Ciencia y Tecnología Agropecuaria, 2022)
The countries of Latin America and the Caribbean (LAC) have made progress in creating and implementing public policies on family farming (FF) by developing their own concepts, which converge in the fact that the family labor force is the most important link. However, this also appears to be their weakness for the future, since the exodus from the countryside to the city is affecting work in this sector, andrestrictive policies in this regard could end up denying the resources needed for FF to achieve greater development. This document aims to review the existing policies, official figures, and regulations that have been created over the years to recognize and strengthen family farming (FF) in Latin America and the Caribbean (LAC). To achieve our goals, we carried out a systematic search for technical documents (books, reports, and papers with official figures), policies, and legislation related to FF in LAC.Several countries have developed concepts to make policies focused on family farmers. Nonetheless, all converge in that the family workforce is the most critical link in this conceptualization. However, it also seems to be its Achilles’ heel for the future since the field-city exodus is affecting this sector, and restrictive policies could reduce the necessary resources for FF to achieve more significant development. Furthermore, the most significant challenges are found in conducting research on crops andanimal species that mainly affect FF, such as corn, beans, rice, cassava, vegetables, cattle, sheep, goats, pigs, and milk. Finally, efforts need to focus on studying changes in family composition, the quality of land, the role of family farmers as guardians of ancestral and native crops, excluding FF export crops. Unpaid women must not be forgotten as a vital part of FF because domestic and production units are closely related.